A fabricated ceiling? - Mora, Nada (2006)
We test whether security prices react to an independent, unanticipated and simultaneous change in the bond rating procedure. It has been problematic in the literature to ascertain whether a borrower's bond price reacts because of a rating change or whether a rating change coincides with a fundamental (or market-perceived) change in the borrower's risk. Moody's unanticipated announcement on June 7, 2001 provides an ideal natural experiment to test for the independent information effect of rating changes. On that date, Moody's eliminated its sovereign ceiling rule allowing a company rating to exceed that of its home country. It placed the long-term foreign currency bonds of 38 companies from 13 different emerging markets, mostly Latin American, on review for an upgrade. We find that the yield spreads of the affected companies fell in a cross-section comparison with control companies on June 8, 2001. However this effect is no longer significant when allowing for a time dimension and not just a limited cross-section comparison on the event date. There is no evidence that companies that a priori would be expected to be more constrained by the sovereign ceiling react more strongly to the announcement. Finally, there is no stock price reaction, even in a cross-section comparison on the event date. That we find little or no security price reaction to Moody's elimination of the sovereign ceiling is a significant result. The sovereign ceiling rule is important to the extent that rating agencies provide information value in pricing emerging market debt. If the independent elimination of the ceiling rule did not contribute new information, then the rule itself may not have been important. There is only one paper that has investigated a change in rating procedures exclusively reflecting rating information. Kliger and Sarig (JOF 2000) assessed the information value provided by Moody's refinement of issued ratings in April 1982. Our paper contributes to this literature on credit ratings as well as to the greater literature on emerging market bonds, which have become the principal source of emerging market finance.